Validation of mammalian target of rapamycin biomarker panel in patients with clear cell renal cell carcinoma. Issue 1 (3rd September 2014) - Haddad, Ahmed Q.; Kapur, Payal; Singla, Nirmish; Raman, Jay D.; Then, Matthew T.; Nuhn, Philipp; Buchner, Alexander; Bastian, Patrick; Seitz, Christian; Shariat, Shahrokh F.; Bensalah, Karim; Rioux‐Leclercq, Nathalie; et al.
Abstract : BACKGROUND: This was an external validation of the prognostic benefit of mammalian target of rapamycin (mTOR) marker panel in patients with clear cell renal cell carcinoma (ccRCC). METHODS: Immunohistochemistry for 5 mTOR pathway markers was performed on tissue microarrays of patients with nonmetastatic ccRCC treated surgically at 4 centers. The markers employed were phosphatase and tensin homolog (PTEN), phosphoinositide 3‐kinase (PI3K), phosphorylated‐mTOR (p‐mTOR), phosphorylated‐S6 (p‐S6), and phosphorylated 4E‐binding protein‐1 (p‐4EBP1). Cox regression was used to correlate marker status and oncologic outcomes. Discrimination of the models was determined using area under the curve and net reclassification improvement. RESULTS: Five hundred twenty‐eight patients with a median follow‐up of 56.5 months were included. Expression of PI3K, PTEN, p‐mTOR, p‐4EBP1, and p‐S6 was altered in 52%, 78%, 25%, 86%, and 30% of patients, respectively. The number of altered biomarkers predicted recurrence‐free survival (RFS) in multivariate analysis adjusted for stage, grade, and lymph node status (HR, 3.20; P = .02 for patients with 4‐5 altered biomarkers compared with 0‐1 altered markers). A biomarker panel consisting of only 2 markers (p‐S6 and p‐4EBP1) independently predicted for worse RFS (HR, 4.38; P = .003 for patients with 2 altered markers compared to patients with 0 altered markers). The biomarker score increased predictive accuracy when added to the clinical Cox regression model. CONCLUSIONS: m‐TOR pathway biomarkers add prognostic information in addition to standard clinicopathologic variables in ccRCC patients and may identify patients who could benefit from additional treatments or closer postoperative surveillance. Cancer 2015;121:43–50 . © 2014 American Cancer Society . Abstract : Alteration of mammalian target of rapamycin biomarkers predicts survival outcomes in patients with clear cell renal carcinoma. This marker panel has prognostic value in addition to standard clinical and pathologic predictors of outcome.